HUBUNGAN PENDIDIKAN KESEHATAN DENGAN PENGETAHUAN TINDAKAN PREVENTIF PENULARAN COVID19 PADA ANAK SD NEGERI 001 KEPENUHAN HULU KABUPATEN ROKAN HULU - Sri Wulandari (Fakultas Ilmu Kesehatan, 2021)
Covid 19 is a new type of disease caused by severe acute respiratory syndrome infection Covid 19 virus 2 (SARSCOV-2) or Covid 19 virus (2019-nCoV). From its inception at the end of 2019 the disease has caused the deaths of 318,789 people worldwide. In their daily activities, children spend their time outdoors. It's just that the limited resources make them still need to get guidance to implement behaviors that become protocols in the prevention of Covid 19. Therefore, health education on Covid 19 knowledge is needed. The purpose of the study was to find out the Influence of Health Education on the knowledge of Covid 19 in Elementary School Children Negeri 001 Kepenuhan Hulu. Pre Experiment Research Design with a sample number of 20 respondents Primary School 001 Kepenuhan Hulu Research Site Data analysis using T Test Dependent The results of the respondent's knowledge research before being given health education with knowledge of Covid 19 the majority are quite as young as 9 people (45%) and after being given education to be good as many as 16 people (80%). After conducting analysis with wilcoxson test obtained overall from respondents experienced increased knowledge with asymp value. Sig. (2-tailed) 0.002 (<0.005) means there is a difference in knowledge before being given health education about Covid 19 to the knowledge of covid 19 with after being given Covid 19 education on covid 19 knowledge. So it can be concluded that there is a significant difference in knowledge before and after being given Health Education about Covid 19. Advice for further researchers to carry out further research on Covid 19 with other variables.